Redevelopment of boat terminal at Kuala Tahan, Pahang - Zubir, Hazwan; Aripin, Srazali; Abdul Rahim, Asiah (IIUM Press, 2023)
Perahu is used significantly by the rural people living on the riverbanks of Malaysia as the main water transport, such as moving from one location to another, transferring foods and agricultural products, fishing and renting it for tourism purposes. However, the usage of perahu as a method of transportation is slowly diminishing. Nonetheless, water transportation service is still dominant for the villagers of Tembeling River, Pahang. The Tembeling River is necessary for the locals and tourists as the route to the remote villages at Hulu Tembeling and National Park, Kuala Tahan. However, deforestation causes damage to the river, which leads to three issues. They are environmental damage, unsustainable economy and loss of culture. Thus, this research aims to redevelop the existing boat terminal at Kuala Tahan, Pahang and enhance the potential ecotourism along the Tembeling River to help prevent excessive deforestation by showing the importance of preserving the nature of Tembeling River. The research aims to improve the existing facilities of the boat services, educate and create awareness of environmental preservation through ecotourism, and preserve the local culture through an architectural approach. The research applied qualitative methods, which consisted of observation and interviews. The secondary data consists of case studies and literature reviews. The findings from the research formulate a design brief to redevelop the existing boat terminal at Kuala Tahan. The proposed design will represent the place as a Gateway to Nature.